A study on the Ego-Integrity - Min, Shinhong (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: As the number of elderly people continued to increase, the state became more concerned with the problems. This study, we tried the basis for developing an intervention to improve Ego-Integrity. Methods/Statistical analysis: The study surveyed 192 elderly people over the age of 65 who were able to communicate and agreed to the purpose of the study among elderly people in the C area. The collected data was performed in SPSS 18.0 descriptive statistics, t- test, ANOVA and correlation analysis. Findings: Among the factors that improve the quality of life of the elderly, the achievement of Ego-Integrity, the developmental challenge of old age, is an important factor in the study. By improving this Ego-Integrity can be achieved successfully aging. Therefore, a method for improving Ego-Integrity is necessary. This study attempted to establish a link between Ego-Integrity and Family Strategy, Life satisfaction of the elderly. Ego-Integrity for the elderly showed a high correlation with Family strength. It has also been shown to be related to life satisfaction. Improvements/Applications: Therefore, we hope to be able to achieve successful aging in the elderly by developing and applying mediation to increase Family strength, Life satisfaction.